Potensi Ekstrak Daun Kelor sebagai Bahan Alami untuk Meningkatkan Karakteristik Sensori Es Krim Fungsional - Breemer, Rachel; Pattiruhu, Gysberth (Universitas Pattimura, 2025)
This study aimed to explore the potential of Moringa oleifera leaf extract on the organoleptic characteristics of functional ice cream. Moringa leaves are rich in bioactive compounds, vitamins, minerals, proteins, and antioxidants that provide health benefits; however, their distinctive green color, strong aroma, and slightly bitter taste may affect consumer acceptance. The research was conducted using a Completely Randomized Design with one factor, namely the concentration of moringa leaf extract (50 g, 100 g, 150 g, and 200 g), each with three replications. The observed variables included color, taste, texture, and overall acceptance, assessed through a hedonic test. Data were analyzed using ANOVA and further tested with the Honest Significant Difference test when significant differences were observed. The results showed that the addition of moringa leaf extract significantly influenced the sensory attributes of ice cream. Treatment A2 (100 g moringa leaf extract) received the highest acceptance level, characterized by a bright green color, balanced flavor without dominant bitterness, smooth texture, and the highest overall score compared to other treatments. Therefore, the A2 formulation can be recommended as the optimal composition for producing functional ice cream with moringa leaf extract that is well accepted by consumers.